Optical spectroscopy of single colloidal CsPbBr3 perovskite nanoplatelets - Huo, Caixia (2020)
Optically bright lead halide perovskite nanocrystals of different morphologies ranging from nanocubes to flat nanoplatelets to elongated nanowires have been reported. The morphology of the nanocrystals is expected to affect various properties such as the band edge energy and the electron-hole exchange interaction. However, aside from nanocubes, the investigation of optical properties in the lead halide perovskite nanocrystals of different morphologies at the single emitter level has been lacking. We have performed optical spectroscopy in single CsPbBr3 nanoplatelets and observed single photon emission without blinking. Furthermore, the photoluminescence emission exhibits excitonic fine structure peaks similar to what has been previously observed in nanocubes. Our work stimulates further investigations into the excitonic and quantum optics properties when the lateral size and morphology can be further controlled in lead halide perovskite nanocrystals.